Prediction of Development of Neonatal Jaundice by Cord Blood Bilirubin and Albumin - Babita Rani; Leesha Kaushik; Preeti Raikwar; Renu Garg; Vijayata Sangwan; Sanjay Kumar Jha; Anita Punia; Deepika Kataria (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2026)
Background: Neonatal jaundice is a common cause of early postnatal readmission and contributes to both financial and socio-economic burden. In resource-constrained nations, where the patient-to-resource-constrained-bed ratio is very high, early prediction of hyperbilirubinaemia will help in early discharge, prevent re-hospitalization, and reduce the duration of hospital stay. This study aims to estimate the cord blood bilirubin (CBB) and albumin (CBA) levels for future prediction of neonatal jaundice among deliveries at Bhagat Phool Singh Government Medical College for Women (BPS GMC (W)). Methods: A prospective study was conducted among 384 randomly selected neonates delivered at BPS GMC (W). Socio-demographic data were recorded, and cord blood samples were collected at birth for bilirubin and albumin estimation. Neonates were followed for 10 days to assess the development of clinical jaundice. Result: Incidence of neonatal jaundice was 21.4% with 10 days of follow-up. 94.8% neonates developed jaundice with CBB level ≥ 2mg/dL, proving it statistically significant. Additionally, 62.7% of neonates with serum albumin < 3 g/dL developed jaundice. Cord blood Bilirubin-to-Albumin ratio proved a good indicator, as area under the curve is 0.933 with sensitivity and specificity of 68.30% and 99.0% respectively at a cut-off level of 0.61. Conclusion: Cord blood bilirubin and bilirubin-to-albumin ratio may help identify neonates at higher risk of subsequent jaundice and may assist in prioritizing follow-up in resource-limited settings. A bilirubin-to-albumin ratio ≥ 0.61 was found to be a highly specific predictor.